Enhancing biomass production and biochemical compositions of Spirodela polyrhiza through superhydrophobic cultivation platforms at low light intensity - Chua, Mei Xia (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.